Lost Sales Inventory Model in Finite Planning Horizon - Gunawan Mangkuharjo; Y. Agustina H; Hui-Ming Wee (Jurnal METRIS, 2014)
This study extends a previous Economic Order Quantity (EOQ) model to include lost sales inventory and afinite planning horizon model. An exact algorithm is developed for finite planning horizon lost salesinventory condition. A practical approach is proposed to derive the optimal solution. The algorithm with lostsales inventory and finite planning horizon method improves the total cost of the inventory policy. Ouranalysis shows that the minimum total cost of the finite planning horizon method is always greater or equalto the infinite planning horizon method.